Women Leadership in Good Corporate Governance Towards Economy Development - Theng In Yen (Jurnal InterAct, 2014)
Globalization has largely influenced women roles within many sectors, especially the economy. More and more women professionals exist in key positions of corporations. However, such phenomenon does not mean that gender disparity and discrimination ceased to exist.   In reality,   the percentage of women obtaining opportunities to actively participate in professional and the economy is still limited and below expectation, although needs to be admitted that such pleasant progress is getting better from time to time. Still, the phenomenon mostly happens in big cities. On the other side, women living in rural areas still have to endure discrimination and repression due to the dominating patriarchy culture. The main factor causing such disparity lies in the lack of education. In fact, the potential of women in leadership is as much as that of men, especially from the view of gender discourse characteristics. Moreover, leadership, which is the main key in good corporate governance, highlights the positive attitudes that lead to the best practices based on effective communication and teamwork while making the best use of technology to compete within the healthy global economic competition. Good governance, which also highlights equality, gives the same opportunities for men and women as well as giving women the opportunities to contribute their potentials for the sake of better economic development. Gender inequality should be understood as the hindrance in the development process,  especially economic development, because belittlement of women potential is the same of paralyzing half of the nation.